Ageing in Urban Neighbourhoods: Exploring Place Insideness Amongst Older Adults in India, Brazil and the United Kingdom. (September 2020) - Woolrych, Ryan; Duvurru, Jamuna; Portella, Adriana; Sixsmith, Judith; Menezes, Deborah; Fisher, Jenny; Lawthom, Rebecca; Reddy, Srikanth; Datta, Anupama; Chakravarty, Indrani; Khan, Abdul Majeed; Murray, Michael; et al.
The ageing in place agenda emphasises the importance of supporting older adults to age in their communities surrounded by the personal resources to age well. In exploring the relationship between older people and their environment, the concept of place insideness is seen as central to constructing feelings of identity, belonging and attachment in old age. Yet there has been little research exploring how older adults experience place insideness across different urban, social and cultural contexts which is an impediment to identifying effective interventions for age-friendly cities and communities. This article explores how place insideness is experienced amongst older adults across India, Brazil and the United Kingdom. The article presents qualitative findings from 294 semi-structured interviews collected across 9 cities and 27 neighbourhoods. The findings reveal that older adults cultivate their sense of place insideness in old age through dimensions of physical insideness (i.e., environmental competence in navigating and engaging in the community), social insideness (i.e., knowing others) and autobiographical insideness (i.e., shared place histories). In drawing on older people's understanding of their communities, this article explores the opportunities and challenges in developing a sense of place insideness to support ageing well. We identify implications for policy and practice in terms of how we can better design urban environments as age-friendly communities which support a greater sense of place for older people.